Diagnostic value of cavernous sinus swelling and extrusion sign in cavernous sinus hemangioma - Guoqing Han; Zhifa Huang; Huanhuan Qiao; Wei Zhu; Xuejiang Yan; Ke Pu; Qingguo Li; Xiaoguang Tong (Heliyon, 2024)
Background and purpose: To examine the diagnostic value of imaging features in cavernous sinus hemangioma (CSH). Materials and Methods: The clinical and imaging data of patients with pathologically confirmed CSH, cavernous sinus meningioma, trigeminal schwannoma and pituitary adenoma invading the cavernous sinus between May 2017 and May 2022 were retrospectively analyzed. The cases were divided into the CSH and non-CSH groups to summarize the magnetic resonance imaging (MRI) characteristics of CSH. Univariate χ2 analysis was performed to assess five indexes, including signal intensity on T2WI, homogeneity of T2WI, enhancement of enhanced T1, enhanced T1 with dural tail sign, and cavernous sinus swelling and extrusion sign. Results: There were significant differences in four features, including hyperintensity on T2WI, homogeneity of T2WI, T1-enhanced without meningeal tail sign, and cavernous sinus swelling and extrusion sign between the CSH and non-CSH groups, with cavernous sinus swelling and extrusion sign showing the most pronounced distinction, with a sensitivity of 100%, a specificity of 93.02%, and an accuracy of 94.23%. The four features could be jointly used as diagnostic criteria, with a sensitivity of 94.44%, a specificity of 100.00%, and an accuracy of 99.04%. Conclusion: Cavernous sinus swelling and extrusion sign is a reliable imaging index for CSH diagnosis. Homogenous hyperintensity or marked hyperintensity on T2WI, enhanced T1 without dural tail sign, and cavernous sinus swelling and extrusion sign could be jointly used as diagnostic criteria, which may improve the accuracy of CSH diagnosis.